Advanced imaging of an incomplete fracture and exostosis of the third metacarpal bone in a young Warmblood horse. (28th May 2018) - Isgren, C. M.; Maddox, T. W.; Blundell, R.; Sinovich, M.; Rubio‐Martinez, L. M.
Summary: A 5‐year‐old Hanoverian gelding with acute moderate right forelimb lameness underwent nuclear scintigraphy, which identified marked increase in radiopharmaceutical uptake of the proximomedial aspect of the right metacarpus. Ultrasonography and radiography identified sclerosis and exostosis of the proximomedial aspect of the metacarpal bone III in‐between the suspensory ligament and the second metacarpal bone, and presence of a suspected fracture. The owner requested euthanasia of the gelding, and post‐mortem computed tomography and magnetic resonance imaging identified marked bone sclerosis and thickening of the palmar cortex of the metacarpal III (McIII), presence of an incomplete fracture in the palmar cortex of McIII and expansive exostosis from McIII extending in a palmar direction between the suspensory ligament and the second metacarpal bone. Histopathological examination confirmed the imaging findings of sclerosis and led to final diagnosis of a fracture of the palmar cortex of the McIII associated with an exostosis encroaching the medial aspect of the suspensory ligament. No abnormalities were present in the suspensory ligament or metacarpal bone II (McII).